CYP27A1-dependent anti-melanoma activity of limonoid natural products targets mitochondrial metabolism. Issue 10 (21st October 2021) - Cho, Hyelim; Shen, Qiong; Zhang, Lydia H.; Okumura, Mikiko; Kawakami, Akinori; Ambrose, Jessi; Sigoillot, Frederic; Miller, Howard R.; Gleim, Scott; Cobos-Correa, Amanda; Wang, Ying; Piechon, Philippe; et al.
Summary: Three limonoid natural products with selective anti-proliferative activity against BRAF(V600E) and NRAS(Q61K)-mutation-dependent melanoma cell lines were identified. Differential transcriptome analysis revealed dependency of compound activity on expression of the mitochondrial cytochrome P450 oxidase CYP27A1, a transcriptional target of melanogenesis-associated transcription factor (MITF). We determined that CYP27A1 activity is necessary for the generation of a reactive metabolite that proceeds to inhibit cellular proliferation. A genome-wide small interfering RNA screen in combination with chemical proteomics experiments revealed gene-drug functional epistasis, suggesting that these compounds target mitochondrial biogenesis and inhibit tumor bioenergetics through a covalent mechanism. Our work suggests a strategy for melanoma-specific targeting by exploiting the expression of MITF target gene CYP27A1 and inhibiting mitochondrial oxidative phosphorylation in BRAF mutant melanomas. Graphical abstract: Highlights: The limonoid, harrpernoid D, was isolated and described Harrperonid D is activated by CYP27A1, to overcome BRAFi-resistant melanoma Metabolism of harrpernoid D into a reactive enedial modifies mitochondrial proteins Abstract : Selective targeting of melanoma cells by limonoid natural products involves their conversion to a reactive electrophilic metabolite by CYP27A1, a mitochondrial cytochrome p450 enzyme, leading to toxic adducts of key mitochondrial proteins. CYP27A1 is a target gene of MITF, the oncogenic transcription factor deregulated in melanoma.